The Influence of Digital Transformation and Customer Experience on Brand Loyalty with Customer Trust as a Moderating Variable from a Marketing 5.0 Perspective - Andika Baskara; Edy Purwanto; Suharti Suharti; Dwi Ari Astono (Universitas KH. Abdul Chalim Mojokerto, 2026)
The purpose of this study is to examine, from a Marketing 5.0 perspective, how digital transformation, customer experience, and trust among customers influence brand loyalty. This study is quantitative and uses a survey methodology for its explanatory design. Semarang City residents who have interacted with brands online and used digital products or services constitute the demographic of this study. One hundred people were surveyed using a non-probability sampling strategy based on a purposive sampling method. Structural Equation Modeling—Partial Least Squares (SEM-PLS) was used for data analysis. Brand loyalty was positively and significantly influenced by digital transformation and customer experience, while consumer trust did not show a substantial direct effect. There was a negative correlation between digital transformation and customer loyalty, although the positive correlation between customer experience and loyalty was mediated by consumer trust. These findings suggest that in the Marketing 5.0 era, trust is a contextual variable that can strengthen or weaken the influence of customer experience and the value of digital transformation on brand loyalty.